On Line Banner Advertising - Sumanjeet (Indian Journal of Marketing, 2005)
Due to emergence and rapid growth of information and communication technology, more and more business activities are shifting to the electronic media. The way business organizations advertise their products or services cannot be exceptions either. Today, online advertising has become a part of companies marketing strategy. There are many forms of online advertising like email, banner, sponsorship, interstitial advertisements, ad. Network, online coupon, etc. But the most common form of online advertising is banner advertising. It can be found in all types of websites with many forms. In fact, it is the oldest form of online advertising. In the beginning, "advertising" on the internet meant "banner-advertising". In 1998 or so, banner advertisement was a lucrative business. According to Internet Advertising Bureau (IAB), banner advertisements accounted for 55% of all online advertisements spending in 1998. And today, also banner advertising is the most popular form of advertising on the Net.